Recobrimentos comestíveis associados a óleos essenciais no controle da antracnose e na qualidade de goiabas ‘Pedro Sato’ - RODRIGUES, Ellen Cristina Nabiça (2021)
This study aimed to assess the potential of edible coatings (COA) based on hydroxypropylmethylcellulose and 20% beeswax combined with essential oils (EOs) in the quality, postharvest conservation, and control of the causative agent of anthracnose (Colletotrichum gloeosporioides) in 'Pedro Sato' guava. In the first experiment, the antifungal potential of EOs was evaluated in vitro for Colletotrichum gloeosporioides. We tested the following EOs: cinnamon (Cinnamomun cassia) at concentrations 0.25, 0.5, 0.75, and 1.0 mL L-1; Thyme (Thymus vulgaris) at concentrations 0.05, 0.1, 0.2, and 0.3 mL L-1; Rosemary (Sage rosmarinus) at concentrations 0.05, 0.1, 0.2, and 0.3 mL L-1; Sweet Basil (Ocimum basilicum) at concentrations 0.5, 1.0, 2.0, and 3.0 mL L-1. In the second experiment, we evaluated the effect of COA combined with the EOs that better performed in the in vitro test. The selected EOs were cinnamon (0.10, 0.25, and 0.50 mL L-1) and thyme (0.10, 0.20, and 0.30 mL L-1). The fruit were inoculated with Colletotrichum gloeosporioides and stored for ten days at 21 ± 1 °C. In the third experiment, the EO of cinnamon was selected, and its concentrations were raised to 1.0 and 1.5 mL L-1. We evaluated the effect of the COA combined with the EO of cinnamon for quality parameters, postharvest conservation, antioxidant activity, and oxidative stress of ‘Pedro Sato’ guava. The findings of the first experiment showed that the EOs of cinnamon and thyme inhibited 100% of mycelial growth and conidial germination of C. gloeosporioides. The EO of sweet basil inhibited the growth of the pathogen in a dose-dependent manner, and the EO of rosemary was not effective at the concentrations tested. In the second experiment, the tested concentrations of cinnamon and thyme combined with COA significantly reduced the incidence of anthracnose in the treated fruit. No significant difference was observed between the concentrations (P > 0,05). However, the EOs presented a difference (P < 0,01) compared to control. The EOs decreased the severity of anthracnose in fruit and less disease incidence. In the third experiment, the COA + EO of cinnamon at 1.0 and 1.5 mL L-1 delayed ripening, maintained peel and pulp color, firmness, soluble solids, titratable acidity, ascorbic acid, and antioxidant activity. Also, the oxidative stress and weght loss of fruit were reduced. The COA + cinnamon EO at 1.0 mL L-1 is the most suitable for potential industrial application. On the sixth day of evaluation, it exhibited physico-chemical characteristics comparable to the control fruit on the first day of storage, contributing to a 4-days gain in the shelf life of guava ‘Pedro Sato'.